Analisis perkawinan usia dini dalam perspektif Maqashid Syari’ah - fadilah, nayla alyatil (Maliki Interdisciplinary Journal, 2026)
Early marriage remains a persistent social issue that affects the well-being of young women in Indonesia. From the perspective of maqāṣid al-sharī‘ah, this practice reflects the inadequate protection of life, intellect, and lineage as the fundamental objectives of Islamic law. This study aims to analyze early marriage through the maqāṣid al-sharī‘ah framework while emphasizing the importance of premarital counseling as a means of preparing couples mentally, spiritually, and socially. This research employs a descriptive qualitative method using a literature study approach by reviewing the most relevant scholarly journals. The findings indicate that early marriage poses various risks, including reproductive health problems, emotional instability, and psychological vulnerability among young brides. From the standpoint of maqāṣid al-sharī‘ah, these conditions contradict the principles of safeguarding life (ḥifẓ al-nafs) and preserving lineage (ḥifẓ al-nasl). The results highlight the need to strengthen education and premarital counseling as preventive measures against child marriage.